Climate Services for Resilient Development in South Asia and Bangladesh: Semi-Annual and Inception Period Report April 2017 - Krupnik, Timothy J.; Hussain, Ghulam; Schulthess, Urs C.; McDonald, Andrew J.; Stirling, Clare M.; Pandit, D.B.; Gerard, Bruno G.; Matin, Mir A; Qamar, Faisal MQ; Fernandes, Jose M.C. (2017)
Developing countries are at considerable risk from climate variability and climate change, both of which threaten poverty reduction and development efforts. The Climate Services for Resilient Development (CSRD) partnership is led by the United States Government has developed a consortium of global leaders in science, technology and development finance to assist at-risk nations to adapt to these problems. CSRD is aligned with the the Global Framework for Climate Services and works in Bangladesh, Ethiopia, and Colombia to creating and provide timely and useful climate data, information, tools, and services. Within South Asia, efforts to develop agricultural climate services under CSRD are led by the International Maize and Wheat Improvement Center (CIMMYT). CSRD in turn works to support Investment Options Paper (IOP) for Climate Services for Resilient Development in Bangladesh, compiled by the Asian Development Bank (ADB) in 2016. CSRD’s core objectives are to prepare farmers, extension services, and agricultural policy makers with actionable climate information and crop management advisories to reduce agricultural production risks and to increase the resilience of smallholder farming communities. This report summarizes CSRD activities, achievements, and challenges during the project’s inception phase (from the end of November 2017 through April of 2017).